THE INFLUENCE OF INTEGRATED COMMUNICATION STRATEGIES IN ONLINEBUSINESS IN THE DIGITAL ERA ON BUILDING AND SUSTAINING CORPORATE IMAGE: A CASE STUDY ON THE DYNAMICS OF COMPANIES IN INDONESIA - Abdul Rosid; Hery Purnomo; A. Hamid; Megandhi Gusti Wardhana; Yanti Setianti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the swiftly evolving digital era, the role of integrated communication strategies in online businesses within the Indonesian context is paramount. This research presents a comprehensive case study examining how these strategies wield influence in shaping and sustaining corporate image. With Indonesia as the backdrop, a dynamic landscape where online businesses thrive, our study offers profound insights into this multifaceted relationship. Approximately 82% of the surveyed online businesses actively engage in integrated communication strategies, transcending conventional communication channels. These strategies coalesce to present a coherent narrative that resonates with the audience. Moreover, 75% of respondents perceive a positive impact on their corporate image due to these strategies. Diving deeper, our findings elucidate the significance of coherence, a customer-centric approach, and continuous adaptation in navigating the digital era. Coherence in communication aligns with values, principles, and ethos. A customer-centric approach underscores the importance of customer satisfaction and loyalty in shaping a positive corporate image. Adaptation signifies a dynamic response to challenges, embracing innovation. The implications of this research extend into the broader landscape of corporate communication and image management in the digitally driven environment. It is a realm where perceptions are not static but dynamic, shaped by each communication endeavor and each online interaction. Challenges coexist with opportunities, and innovation thrives. Integrated communication strategies are instrumental in crafting a corporate identity that resonates with stakeholders and fortifying a favorable corporate image. This research offers businesses a compass to navigate the complexities of the digital era, aligning their narratives with their core values and principles to build and sustain a resilient corporate image.